2022
DOI: 10.1111/joss.12788
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation in the personal care space: A review

Abstract: Personal care encompasses a diverse set of product categories including primarily skincare, makeup, and haircare, among others. With such varied use occasions and application styles, researchers require less traditional sensory and consumer research methods for product evaluation including a combination of interviews, focus groups, descriptive analysis, consumer research, and instrumental testing. More novel methods, such as emotion and online review research, provide sensory scientists with new avenues for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In line with this, conventional sensory panels comprising experts who are highly trained in providing detailed taste descriptions, which are often required in ensuring quality assurance for food, perfumes, wines, and beer [ 31 , 32 , 33 ], may not be necessary for paediatric formulation development. However, numerous studies have indicated that trained assessors do outperform consumers, primarily due to their familiarity with experimental procedures used for sample evaluation [ 34 ] and their ability to articulate their taste perceptions [ 35 ].…”
Section: Human Taste Panelmentioning
confidence: 99%
“…In line with this, conventional sensory panels comprising experts who are highly trained in providing detailed taste descriptions, which are often required in ensuring quality assurance for food, perfumes, wines, and beer [ 31 , 32 , 33 ], may not be necessary for paediatric formulation development. However, numerous studies have indicated that trained assessors do outperform consumers, primarily due to their familiarity with experimental procedures used for sample evaluation [ 34 ] and their ability to articulate their taste perceptions [ 35 ].…”
Section: Human Taste Panelmentioning
confidence: 99%
“…The need for sensory research application on consumer products in the non‐food category has been promoted at various conferences such as the 2018 and 2020 Society of Sensory Professionals conferences (Sabanos, 2020; Van Haren et al, 2018). Sensory research on non‐food products has expanded to various categories such as textiles, personal care, automobiles, fragrances, and so forth (Deubler et al, 2022; Duthoit‐Saint Georges & Lemercier‐Talbot, 2022; Nagamatsu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%